2023
DOI: 10.1111/asj.13819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rutin supplementation on growth performance, slaughter performance, serum parameters, and meat quality of Nubian goats

Abstract: Previous studies found that rutin can improve production performance of sheep and dairy cows. However, it is not clear whether rutin has similar effects in goats. Hence, the aim of this experiment was to study the effects of rutin supplementation on growth performance, slaughter performance, serum parameters, and meat quality of Nubian goats. A total of 36 healthy Nubian ewes were randomly divided into three groups. Goats were fed the basal diet supplemented with 0 (R0), 25 (R25), and 50 (R50) mg rutin per kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Slaughter performance, including carcass weight and dressing percentage, directly manifests the growth performance and economic value of animals [ 5 , 15 ]. Differences among treatments in SBW, EBW, HCW, net meat percentage, the ratio of meat to bone, and visceral fat percentage were observed at both stages in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slaughter performance, including carcass weight and dressing percentage, directly manifests the growth performance and economic value of animals [ 5 , 15 ]. Differences among treatments in SBW, EBW, HCW, net meat percentage, the ratio of meat to bone, and visceral fat percentage were observed at both stages in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A balanced nutritional feed has been found to promote the growth and development of dairy goats, improving their milk production performance during lactation [ 4 ]. Adequate protein intake also enhances their growth rate and muscle development [ 5 , 6 ]. Research on organ development in dairy goats has primarily focused on the mammary gland and digestive system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rutin, or rutoside, quercetin-3- O -rutinoside, or vitamin P, is a natural flavonoid glycoside that is a secondary metabolite in plants, which has antioxidant, anti-hypertension, anti-diabetes, anti-inflammation, and cardioprotective functions. Previously, we reported that rutin promoted the growth performance of sheep by enhancing antioxidant capacity and rumen fermentation and regulating hormone secretion, and improved meat quality of goats [ 4 – 6 ]. These studies indicate that rutin might be used in ruminant production as a feed additive.…”
Section: Introductionmentioning
confidence: 99%